O papel da liderança na gestão de ações coletivas: um estudo teórico e empírico em organizações agroindustriais da microrregião de Toledo/PR - Wenningkamp, Keila Raquel (2019)
This research covers the role of leadership in collective action management. This type of organization refers to the complex forms of governance between market and hierarchy that emerge as a response to a set of transactions performed collectively by individuals and firms in order to achieve goals that are unlikely to be achieved individually. In the agroindustrial field, cooperatives, associations, clusters, local productive arrangements and networks are examples of the collective actions. These organizational forms have peculiar characteristics, whose efficient management becomes a challenge, because unlike the management of hierarchical organizations, there is a need to manage agents who are both autonomous and interdependent. In this sense, leadership (as one of the elements of management) becomes essential for the formation and maintenance of collective actions over time, in order to favor the achievement of individual and group goals. However, despite being pointed as important, the role of leadership in the management of collective actions is still little explored. Thus, the objective of this research is to understand the role of leadership in the management of collective actions based on the construction of a theoretical-methodological model and an empirical multi-case study in agro-industrial organizations of the Toledo-PR Microregion. In methodological terms, this research is a bibliographic, field and multicase study of the descriptive character. The empirical data is based on documents, interviews and questionnaires directed to leaders and led in both an association (smaller group) and a cooperative (larger group), whose analysis is descriptive and exploratory (descriptive statistics). The main results can be presented in two forms: theoretical and empirical. Regarding the results obtained from the theoretical construction, it can be said that the role of leadership is focused on relationships, whose main focus is to influence and involve members of collective action to collaborate and cooperate in the achievement of collective objectives linked to the individual purposes. Thus, this role involves 14 aspects brought together in three sets: relationship (Communication, Motivation, Mediation, Trust, Innovation, Support, Influence and Empowerment), control (Monitoring/Evaluation, Incentives and Sanctions, Regulation and organization) and planning (Alignment of individual and collective goals, Collective Identity and Vision/direction). These factors are different from management, since this is broader and includes, in addition to relationships (leadership), aspects related to the structure and organizational processes. Furthermore, even though some of these 14 items may converge to functions similar to those of leadership in hierarchical organizations, they differ in the sense of how they should be performed, given that they are attributions exercised in organizations whose property belongs to all (the members and associates, for example).In terms of empirical results, it can be concluded that the members of the two collective actions agree on the factors that make up the leadership role. However, they do not totaly see the exercise of these attributions in practice, denoting a gap between what should be a leadership role and what is actually being performed by leaders and/or perceived by those led. In addition, members of the smaller group (the association) perceive leadership more than the members of the larger group (the cooperative). Besides that, it was observed that leaders differ from their perceptions of how much the role of leadership is present in their collective actions, and leaders of the larger group perceive more the practice of their functions than those led, with contrary in the smaller group. Finally, suggestions for actions and reflections are made in order to contribute to greater effectiveness of leaders in the management of collective actions.